Entry Points to Improve Livestock Water Productivity in Selected Forage Based Livestock Systems - Haileslassie, Amare; Descheemaeker, Katrien K.; Blümmel, Michael; Craufurd, Peter Q.; Ergano, Kebebe (International Livestock Research Institute, 2013)
Agricultural production is challenged by increasing water scarcity and simultaneously growing demands for food and feed. Globally livestock feed sourcing is seen as one of the major causes for water depletion, and therefore increasing livestock water productivity (LWP) is necessary. Feed sources in Forage Based Livestock Production Systems [FLPS (grazing, mixed-irrigated and mixed-rainfed)] largely consist of pasture, crop residue, or immature cereal crops, and also plants cut for fodder and carried to the animals. In drylands (arid and semi-arid) eco-regions, FLPS are generally extensive and thus the scale of water depletion for feed production is a major concern. This paper synthesizes LWP-knowledge generated across different FLPS over time and systematically identifies entry points to enhance productive uses of fresh water resources. It draws on examples of grazing systems in Uganda (Nile basin), mixed-rainfed systems in Ethiopia (Nile basin), mixed-irrigated systems in Sudan (Nile basin), and mixed-irrigated systems in India (Indio-Gangana basin). Although these systems vary by their degree of intensification, scale of water related problems, and therefore in their values of LWP, a number of common entry points to increase LWP can be identified. Based on empirical evidence from these systems, we systematically clustered these entry points as: (1) improving the water productivity of feed; (2) improving livestock feed sourcing and feeding; (3) enhancing livestock feed use efficiencies; and (4) enabling institutions and market linkages to facilitate adoption of relevant technologies. The paper concludes by discussing a comprehensive framework for entry points to improve water productivity in FLPS.